STRATEGI KOMISI PEMILIHAN UMUM DALAM MENEKAN ANGKA GOLPUT PADA PEMILIHAN WALI KOTA MAKASSAR - Mahfud, Mahfud; Sultan, Lomba (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
The high number of abstentions causes a low level of trust and credibility of the elected candidates. As a result, local governments cannot carry out their functions properly due to a lack of political support. This study aims to determine the General Election Commission’s strategy in suppressing abstentions in Makassar City. The type of research used is field qualitative research with a juridical approach. The results of the study show that the practice of abstentions in Makassar City is classified into three groups including ideological abstentions, political abstentions and practical abstentions. Therefore, the Makassar City Election Commission’s strategic efforts in suppressing and overcoming the high number of abstentions in Makassar City include: 1) ensuring that citizens are registered on the voter list; 2) election socialization and education and awareness of democracy to the people and 3) formation of Makassar democracy volunteers.